A quasi-public sphere - Fiedler, Anke (Javnost (Ljubljana), 2015)
Using the example of the German Democratic Republic, the present article argues that communist leadership established a non-public communication channel between politics, administrations, industry and the population that took on most of the functions of the non-existent public sphere: letters to the editor. By law, those letters were considered petitions. The editorial offices had to register and answer them in a timely manner or transmit them to the authorities for consideration. This policy of focusing on individual cases while avoiding public sphere levels of mass communication and public meetings had two advantages for the ruling communist party: Critics were satisfied and "kept quiet" and other people were left in the dark unless they heard rumours during "encounters". Those in power accepted that the absence of a critical discursive space hampered the process of innovation and social change-setting the German Democratic Republic apart from countries with autonomous media systems. The petition "solution" could only work as long as the number of critical readers letters remained within a reasonable limit, something that became impossible during the crisis of the late 1980s.
Keywords: Editors; German Democratic Republic; Javna sfera; Nemška demokratična republika; peticije; petitions; Political communication; Politično komuniciranje; Public sphere; Uredniki